(untitled) (Al-Academy, 2018)
This research is the subject of "Domination and Motivation in the Sculptures of Mona the Saudi" to the study of an accomplished Arab sculptor with its varied sculptural activity between the works of the exhibition and the works of the squares, as well as its distinguished place among the contemporary Arab sculptors. This research is divided into four chapters: The first chapter deals with the general methodological framework of the research in terms of the research problem which is focused on the question: What is the hegemony and motivation in the sculptures of Mona Saudi? The importance of research and the need for it, including the technical scientific material concerned with the sculptural achievement of the Jordanian sculptor Mona Saudi as it is an important unit in the movement of contemporary Arab sculpture and including this achievement of the elements of dominance and motivation as two important processes can lend the nature of expressive form and content, Domination and motivation in the sculptures of Mona Saudi. The temporal limits for the period (2002-2012) and the limits of spatial presence of these works of sculpture inside or outside the Arab world. This chapter also identifies some important terms in the research.